2012
DOI: 10.1186/1475-2891-11-71
|View full text |Cite
|
Sign up to set email alerts
|

Popcorn is more satiating than potato chips in normal-weight adults

Abstract: BackgroundStrategies that may increase compliance to reduced energy intakes are needed to reduce the health burden of obesity. Conflicting evidence exists regarding the effects of snacking on satiety and energy intake.MethodsThis study compared short-term satiety from two common snack foods, low fat popcorn or potato chips. Using a counterbalanced within-subject design, 35 normal weight non-smoking participants (17 men, 18 women) ages 20–50 years (mean age 33 ± 11, BMI 23 ± 2 kg/m2) consumed four conditions ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Popcorn is a popular food in the United States; Americans consume, on average, 15 billion quarts of popcorn annually, 70% of which is home popped and prepopped 48. Popcorns, as a whole grain food, are known to contain relatively higher amounts of fiber and have a higher satiety index than other commonly consumed snacks, such as potato chips 4950. Unhealthful ingredients, such as salt, butter, and sugar, are often added during commercial processing of popcorns, however, and thus many brands of popcorns sold in United States are classified as ultraprocessed foods 515253.…”
Section: Discussionmentioning
confidence: 99%
“…Popcorn is a popular food in the United States; Americans consume, on average, 15 billion quarts of popcorn annually, 70% of which is home popped and prepopped 48. Popcorns, as a whole grain food, are known to contain relatively higher amounts of fiber and have a higher satiety index than other commonly consumed snacks, such as potato chips 4950. Unhealthful ingredients, such as salt, butter, and sugar, are often added during commercial processing of popcorns, however, and thus many brands of popcorns sold in United States are classified as ultraprocessed foods 515253.…”
Section: Discussionmentioning
confidence: 99%
“…A fructo-oligosaccharide-enriched cookie produced greater ratings of satiety than a control cookie, which showed the potential contribution of fructo-oligosaccharides to satiety (50). Another study compared short-term satiety from low-fat popcorn with potato chips, without making any alterations to their nutrient composition (51). Participants expressed less hunger, more satisfaction, and lower estimates of prospective food consumption after 6 cups of popcorn than after consumption of the potato chips.…”
Section: Snack Foods and Satietymentioning
confidence: 99%
“…Potato chips are very high in energy density (383-574 kcal/100g) and have a low satiety index, yet they are commonly consumed as snacks. 35,42 Our results showed that an increased intake of potatoes not cooked in oil-in contrast to French fries and potato chips-was not significantly associated with excess weight gain. .…”
Section: Discussionmentioning
confidence: 55%